Prevention and correction of violations of posture in the required classes of physical training on the department of the athletics - Gavrilova N.M; Bochkova N.L (Kharkov National Pedagogical University, 2010)
Article is dedicated to the substantiation of the use of exercises, directed toward preventive and correction of the violations of posture, on the required classes of physical training. The state of the problem of prevention and correction of violations of student's posture was studied according to literature data scientific methods. The athletics is characterized by the variety of the utilized exercises and by a large quantity of methods and versions of their fulfillment, which makes these occupations optimal for the solution of the problems of prevention and correction of violations of posture. It is recommended to use special exercises for the prevention and correction of violations of posture on the athletics classes.